2002
DOI: 10.1016/s0927-7757(02)00142-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of water-soluble cationic porphyrins in sol–gel silica matrices and coatings

Abstract: Silica aeorogels doped with different concentrations of water-soluble cationic porphyrins were synthesised by the sol-gel polymerisation of tetraethylorthosilicate (TEOS). Porphyrin dimer formation in sol-gel matrices was studied in the function of gelation time, over the porphyrin concentration range up to 10 − 5 M. The deviation from the linearity of Beer-Lambert law starts with porphyrin concentration about 5 ×10 − 6 M. The dimerization constants were estimated. The similar dependence could be observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The changes in the distribution of the Q band components, mainly Q(1, 0) suggest competition between the quenching and the internal conversion processes in populating of the emitting level. Partial dissociation and racemization processes of the porphyrin can also play certain role [21,23]. At this stage of the investigations, it is difficult to evaluate the net effect of the respective processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the distribution of the Q band components, mainly Q(1, 0) suggest competition between the quenching and the internal conversion processes in populating of the emitting level. Partial dissociation and racemization processes of the porphyrin can also play certain role [21,23]. At this stage of the investigations, it is difficult to evaluate the net effect of the respective processes.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor influencing absorption and emission spectra of porphyrins is pH. Recently, Dargiewicz et al [23] showed the relation between pH and changes in the absorption spectra of porphyrines in different media (water, alcohol, silica sol-gel). The authors suggest the potential applications of films (obtained by the dip-coating method) containing cationic water-soluble porphyrins as the pH sensors.…”
Section: Resultsmentioning
confidence: 99%
“…The Soret band is redshifted (440-465 nm) with respect to the absorption maximum observed for the dye solution (420 nm). This trend has been repeatedly observed for similar systems, including dye/clay aqueous dispersions [5,22,23]. There is still no agreement on the interpretations of the spectral changes.…”
Section: Xrd Analysismentioning
confidence: 77%
“…The most spectacular examples of spectroscopic properties of porphyrin intercalates are reported below. Dargiewicz et al (2002) studied the UV-Vis absorption spectra of water soluble porphyrins: tetrakis[4-(trimethylammonio)phenyl] (H 2 TTMePP) and tetrakis(1-methyl-4-pirydyl)( H 2 TmePyP) in the monolith silica aerogel and solid thin films obtained by the sol-gel method (Figs. 7-8).The authors found the bands intensity decrease, their broadening and shift in both porphyrins toward longer wavelengths when the sol solution was compared with the aerogel and monolithic sol-gel material.…”
Section: Spectral and Biocatalytical Properties Of Porphyrins Immobilmentioning
confidence: 99%